Small molecule inhibitors of fungal Δ(9) fatty acid desaturase as antifungal agents against Candida auris - Tebbji, Faiza; Menon, Anagha C. T.; Khemiri, Inès; St-Cyr, Daniel J.; Villeneuve, Louis; Vincent, Antony T.; Sellam, Adnane (Frontiers in Cellular and Infection Microbiology, 2024)
Candida auris has emerged as a significant healthcare-associated pathogen due to its multidrug-resistant nature. Ongoing constraints in the discovery and provision of new antifungals create an urgent imperative to design effective remedies to this pressing global blight. Herein, we screened a chemical library and identified aryl-carbohydrazide analogs with potent activity against both C. auris and the most prevalent human fungal pathogen, C. albicans. SPB00525 [N’-(2,6-dichlorophenyl)-5-nitro-furan-2-carbohydrazide] exhibited potent activity against different strains that were resistant to standard antifungals. Using drug-induced haploinsufficient profiling, transcriptomics and metabolomic analysis, we uncovered that Ole1, a Δ(9) fatty acid desaturase, is the likely target of SPB00525. An analog of the latter, HTS06170 [N’-(2,6-dichlorophenyl)-4-methyl-1,2,3-thiadiazole-5-carbohydrazide], had a superior antifungal activity against both C. auris and C. albicans. Both SPB00525 and HTS06170 act as antivirulence agents and inhibited the invasive hyphal growth and biofilm formation of C. albicans. SPB00525 and HTS06170 attenuated fungal damage to human enterocytes and ameliorate the survival of Galleria mellonella larvae used as systemic candidiasis model. These data suggest that inhibiting fungal Δ(9) fatty acid desaturase activity represents a potential therapeutic approach for treating fungal infection caused by the superbug C. auris and the most prevalent human fungal pathogen, C. albicans.